2010
DOI: 10.1073/pnas.1009532107
|View full text |Cite
|
Sign up to set email alerts
|

T-type channels control the opioidergic descending analgesia at the low threshold-spiking GABAergic neurons in the periaqueductal gray

Abstract: Endogenous opioids generate analgesic signals in the periaqueductal gray (PAG). However, because cell types in the PAG are difficult to identify, its neuronal mechanism has remained poorly understood. To address this issue, we characterized PAG neurons by their electrical properties using differentially labeled GABAergic and output neurons in the PAG. We found that GABAergic neurons were mostly fast-spiking cells and could be further divided into two distinct classes: with or without low-threshold spikes (LTS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 32 publications
1
66
0
Order By: Relevance
“…117,118 The analgesic effects are mediated by serotonergic fibers arising from the PAG. Serotonergic neurotransmission in the PAG is inhibited by local GABAergic neurons.…”
Section: Molecular Changes In the Periaqueductal Graymentioning
confidence: 99%
“…117,118 The analgesic effects are mediated by serotonergic fibers arising from the PAG. Serotonergic neurotransmission in the PAG is inhibited by local GABAergic neurons.…”
Section: Molecular Changes In the Periaqueductal Graymentioning
confidence: 99%
“…Thus, we recorded the discharge activity of GABAergic neurons in MS slices at −50 mV for 1 min. This experiment was based on previous reports that maintaining the membrane potential at around −50 mV generates spontaneous-like discharge activity in neurons (30). The discharge activity of septo-hippocampal GAD67 + GABAergic neurons in WT mice was very low, 0.084 ± 0.049 Hz (Fig.…”
Section: Generalizedmentioning
confidence: 99%
“…Thalamic relay cells fire in two distinct modes, burst or tonic, which are dictated by the state of low-threshold, voltage-gated, T-type Ca 2+ channels (39,40). Using Ca v 3.1 −/− mice, we previously demonstrated that the deletion of Ca v 3.1 T-type currents results in the absence of LTS and an increase in tonic firing in periaqueductal GABAergic neurons (30), whereas enhanced expression of T-type currents decreases tonic firing activity in thalamic relay neurons (41). In the present study, using null-mutant and MS-specific knockdown of Ca v 3.1, we demonstrated that Ca v 3.1 T-type Ca 2+ channels are involved in the Representative LFP waveforms and (E and F) corresponding averaged power spectra recorded during urethane anesthesia's theta-on state and wheel-running, respectively, in mice during the period of no application of light (black trace) and photo-inhibition period (blue trace) (n = 6).…”
Section: Optogenetic Modulation Of Septo-hippocampal Gabaergic Fibersmentioning
confidence: 99%
“…The LJP was corrected offline. vlPAG neurons were first identified either as projecting neurons or as interneurons, on the basis of their intrinsic membrane properties, and further classified as FS or TS according to the criteria described elsewhere (Park et al, 2010) (details in the Supplementary Material). .…”
Section: Patch-clamp Recordingsmentioning
confidence: 99%